Toward a Longitudinal, Multi-Dimensional Class Model - James C. Witte (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
A longitudinal analytical framework, one that sees class as a process over time and not a fixed attribute, is proposed as a means to redirect class analysis and revive a theoretical debate that has gone stale. Class analysis implies an inherently dynamic perspective. However, quantitative studies of class that go beyond static analyses of cross-sections are rare. Three dimensions of class may be identified in previous work on the effects of class: 1) class as market situation, 2) class as social status, and 3) class as position in the relations of production. A longitudinal multi-dimensional model would allow each of these aspects of class to independently influence the life course over time. Hierarchical Linear Modeling (HLM) techniques are used to estimate a model of this type. Thirteen years of individual income data from the German Socio-Economic Panel (GSOEP) are used to illustrate the application of this framework. The estimate results indicate that each of the three dimensions significantly affects income trajectories over time, but they do so in different ways.
Keywords: 330; Soziale Schicht; Intertemporale Einkommensverteilung; Sozialstruktur; Deutschland